2018
DOI: 10.5296/ijld.v8i3.13447
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Service Quality on Students’ Satisfaction in a Ghanaian Public Tertiary Institution

Abstract: This study aims at exploring the relationship between service quality dimensions and overall service quality dimensions (tangibility, responsiveness, reliability, assurance and empathy) and students satisfaction. Additionally, this study also looks at the critical factors in service quality dimensions that contribute most to the satisfaction of the students. The data was collected using a set of questionnaire from 798 undergraduate students who offered various bachelor degrees in a public higher education inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…This is consistent with a study done in Ghana, which assessed the student's satisfaction with the quality of service offered by the public higher education institutions. 26 However, this result was lower than the international students satisfaction 27 and physiotherapy students of Taif University, Saudi Arabia. 28 The possible reasons could be that physiotherapy education in Ethiopia is relatively new when compared to the other countries.…”
Section: Discussionmentioning
confidence: 72%
“…This is consistent with a study done in Ghana, which assessed the student's satisfaction with the quality of service offered by the public higher education institutions. 26 However, this result was lower than the international students satisfaction 27 and physiotherapy students of Taif University, Saudi Arabia. 28 The possible reasons could be that physiotherapy education in Ethiopia is relatively new when compared to the other countries.…”
Section: Discussionmentioning
confidence: 72%
“…This study discloses reasonable results to conclude that student satisfaction is affected by both academic and non-academic services. Previous studies on this area also found a significant positive relationship between these variables in different contexts (Eshun et al, 2018;Hassan et al, 2019). However, most of the studies focused on the effects of academic service on student satisfaction (Manik & Sidharta, 2017;Hassan et al, 2019;Hwang & Choi, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…However, the results of this study cannot be taken as independent of other factors present in the regular university environment, which also plays a role in student satisfaction. But as the global competitiveness in higher education is growing worldwide, one can understand the importance of these variables for student satisfaction (Eshun et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the modified SERVQUAL Theory has been used extensively to measure service quality and satisfaction mainly in the banking sector (Pakurár et al 2019), it is important to note that the SERVQUAL Theory is an appropriate assessment tool for measuring service quality perceptions of clients generally. A few studies on DE in the Ghanaian context have been cited to use the SERVQUAL Theory (Eshun, Badu, and Korwu 2018;Gonu and Agyepong 2016). Given the gap identified and the fact that the modified SERVQUAL model has proven to be an effective tool to assess service quality globally, we deem it appropriate to assess the dimensions of the UG DE service quality from students' perspectives.…”
Section: Introductionmentioning
confidence: 99%